Giving Effective Feedback: A Faculty Development Online Module and Workshop - Eva Aagaard; Zuzanna Czernik; Charles Rossi; Gretchen Guiton (Association of American Medical Colleges, 2010)
Abstract Introduction Studies have shown that trainees want feedback and that constructive and specific feedback can improve a trainee's performance. Despite its clear importance, effective feedback giving is not always formally taught. This set of resources was designed to explain the components of effective feedback and to provide evidence-based tips on how to give good feedback. In order to address any limitations of the online module format, we also developed a workshop that provides interested individuals with the opportunity to practice these skills, ask questions, and discuss topics learned. Methods This resource was created as a series of faculty development options to teach residents, fellows, and faculty how to give feedback effectively. Included are the content from an online module and an elective workshop. Results The online module was required for all incoming interns, residents, and fellows at our institution and is now being offered as a voluntary resource for similar audiences elsewhere. The workshop was given to all incoming interns and repeated throughout the year for interested residents, fellows, and faculty. We have some preliminary survey data from these workshop sessions showing that the material was well received, with 72% of those surveyed (n = 266) stating that they either agreed or strongly agreed that the "information was useful" and that they "will use this information in the next year." Discussion We plan to assess the impact of the resource on student and resident feedback as assessed by faculty assessments and course evaluations. In addition, we plan to create similar modules and workshops on a variety of teaching skills over the coming year in hopes of creating a comprehensive faculty development offering for everyone who teaches medical trainees at the University of Colorado School of Medicine.